Purchasing-Power-Parity and the Saving Behavior of Temporary Migrants - Alpaslan Akay; Alexandra Brausmann; Slobodan Djajic; Murat G. Kirdar (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2019)
How does the saving behavior of immigrants respond to changes in purchasing power parity between the source and host countries? We examine this question by building a theoretical model of joint return-migration and saving decisions of temporary migrants and then test its implications by using data from the German Socioeconomic Panel on immigrants from 92 source countries. As implied by our theoretical model, we find that the saving rate increases in the price of host- in terms of source-country currency, but decreases in the source-country price level and that the absolute magnitude of both relationships increases as the time to retirement becomes shorter. At the median level of years to retirement, the absolute values of the elasticity of savings with respect to the nominal exchange rate and with respect to the source-country price level are both close to unity. Moreover, as we gradually restrict the sample to individuals with stronger return intentions, the estimated magnitudes become larger and their stastical significance higher.
Keywords: F22; J61; 330; Migrants' Savings; Return Migration; Exchange Rates; Prices; PPP